2022
DOI: 10.3889/oamjms.2022.7697
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combination of Pelvic Rocking Exercise and Back Massage to Pain and Duration of Labor in Primigravidae

Abstract: Background The combination of pelvic rocking exercise using a birth ball and back massage as non-pharmacological therapy needs to be investigated in relation to reducing pain and labor duration in primigravida mothers.   Aim This study aims to determine the effect of a combination of pelvic rocking exercise using a birth ball and back massage on pain and labor duration in primigravida mothers.    Methods The design of this study was quasy Experiment with the approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…Gonenc and Terzioglu declared that there were no significant differences between the acupressure and massage groups and the control group in terms of delivery time [19] that is similar to the result of this study. Sulistiningsih et al (2022) reported a significant reduction in duration of labor, in contrary to the current study [12].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Gonenc and Terzioglu declared that there were no significant differences between the acupressure and massage groups and the control group in terms of delivery time [19] that is similar to the result of this study. Sulistiningsih et al (2022) reported a significant reduction in duration of labor, in contrary to the current study [12].…”
Section: Discussioncontrasting
confidence: 99%
“…Baljon et al in 2022 declared that massage lowered labor pain intensity and anxiety [11]. In another study combination of pelvic rocking and back massage had a significant effect on pain and duration of labor [12]. Performing massage also accompanied by fewer requests for epidural analgesia [13].…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted in primiparous pregnant women, when the effect of pelvic swing exercises and back massage combination on labor pain was examined, the duration of labor was found shortened and labor pain was reduced. 54 Studies have reported that pregnant women using a birth ball have signi cantly lower levels of pain compared to other pregnant women [11,22,34]. In studies examining the effect of birth ball on birth outcomes, labor pain was found to be lower in pregnant women who used a birth ball during labor compared to those who did not.55,56 In the study examining the effect of the birth ball used with breathing techniques in the rst stage of labor on labor pain, it was found that the combined method reduced labor pain in the intervention group [54].…”
Section: Discussion Of the Intervention And Control Group's Vas Scoresmentioning
confidence: 99%
“…In another study conducted in primiparous pregnant women, when the effect of pelvic swing exercises and back massage combination on labor pain was examined, the duration of labor was found shortened and labor pain was reduced. 54 Studies have reported that pregnant women using a birth ball have signi cantly lower levels of pain compared to other pregnant women [11,22,34]. In studies examining the effect of birth ball on birth outcomes, labor pain was found to be lower in pregnant women who used a birth ball during labor compared to those who did not.55,56 In the study examining the effect of the birth ball used with breathing techniques in the rst stage of labor on labor pain, it was found that the combined method reduced labor pain in the intervention group [54].…”
Section: Discussion Of the Intervention And Control Group's Vas Scoresmentioning
confidence: 99%
“…54 Studies have reported that pregnant women using a birth ball have signi cantly lower levels of pain compared to other pregnant women [11,22,34]. In studies examining the effect of birth ball on birth outcomes, labor pain was found to be lower in pregnant women who used a birth ball during labor compared to those who did not.55,56 In the study examining the effect of the birth ball used with breathing techniques in the rst stage of labor on labor pain, it was found that the combined method reduced labor pain in the intervention group [54]. It was determined that the results obtained from our research are in parallel with the relevant literature.…”
Section: Discussion Of the Intervention And Control Group's Vas Scoresmentioning
confidence: 99%